Validation of CYR-1 marker linked with yellow mosaic virus resistance in black gram (Vigna mungo L. Hepper) - Panigrahi, K. K.; Das, T.R.; Baisakh, B.; Mohanty, A.; Pradhan, J. (The Indian Journal of Genetics and Plant Breeding, 2016)
The inheritance of yellow mosaic virus (YMV) resistance was studied in blackgram using the molecular marker and F2 population derived from the cross Keonjhar Local(susceptible) × OBG-31(resistant). Assuming Mendelian inheritance, almost perfect fit to a ratio of 3S:1R in segregating population suggested a single recessive gene controlling YMV resistance in V. mungo. The presence of recessive gene was further confirmed by the linked DNA marker of 1236 bp named ‘CYR1’. Amplification of CYR1 marker from the genomic DNA of phenotypic resistant individuals from segregating F2 populations and F3 families revealed a tight linkage between this marker with the YMV resistance.